Rare bird documentation form for Northern Goshawk at MacBride Field Campus, 1983 - Newlon, Carol S.et al (1983)
Rare bird documentation form for two Northern Goshawks at MacBride Field Campus in Johnson County, IA on December 17, 1983. Epson - sheet feed